2013
DOI: 10.1111/jfbc.12035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Carp Antioxidant Peptide on the Lipid Oxidation of Sierra Fish Fillets (Scomberomorus Niphonius ) during Frozen Storage

Abstract: Sierra fish fillets were subjected to 1.5% silver carp antioxidant peptide (SAP) solution, 0.5% carnosine solution, 0.02% propyl gallate (PG) solution and distilled water individually for 1 h at 4C and subsequently stored at -18C for 150 days. At regular intervals, the thiobarbituric acid reactive substances (TBARS), conjugated diene (CD) value, free fatty acid content, free fatty acid composition, fluorescence compound and a-tocopherol were determined. Results showed that SAP could reduce free fatty acid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…For instance, antioxidative peptides could serve as ingredients in food product formulations for the prevention, delay, control, and/or management of oxidative stress‐related disease conditions. In addition, antioxidant peptides could also serve as additives in foods in order to curb the oxidation of food products (Qiu, Chen, & Dong, ). This is especially useful to prevent oxidative rancidity of foods containing oils where the formation of ketones and aldehydes could impair the food's organoleptic properties, shorten its shelf life and result in considerable economic losses (He et al, ; Nwachukwu & Aluko, ; Qiu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, antioxidative peptides could serve as ingredients in food product formulations for the prevention, delay, control, and/or management of oxidative stress‐related disease conditions. In addition, antioxidant peptides could also serve as additives in foods in order to curb the oxidation of food products (Qiu, Chen, & Dong, ). This is especially useful to prevent oxidative rancidity of foods containing oils where the formation of ketones and aldehydes could impair the food's organoleptic properties, shorten its shelf life and result in considerable economic losses (He et al, ; Nwachukwu & Aluko, ; Qiu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that dip treatments significantly decreased the formation of PV and TBARS over a 90‐h storage at 4 °C compared to dipping in water (control); no significant difference was seen between either whole hydrolysate and <10 kDa fractions, or between 2‐ and 4‐min treatments. A profound difference between the studies by Dekkers et al ., ; and Qiu et al ., , and our study is the abundance of peptides in the two former; the PJ we used is a mixture of non‐hydrolysed sarcoplasmic proteins and LMW muscle compounds with the only peptides present being endogenous ones (Sannaveerappa et al ., ). In the previous studies of herring and cod light muscle PJ (Undeland et al ., ; Sannaveerappa et al ., ), investigations of underlying antioxidant mechanisms revealed that the <1 kDa fractions of whole and heat‐treated PJs were found to be as inhibitory towards lipid oxidation as the unfractionated PJs, indicating that LMW substances were being the responsible antioxidative components.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analyses, and to some extent also analyses of redness and rancid odour, further showed that exchanging water with another solution, or making additions into the water can further protect against oxidation when fillets are stored beyond 6 months. Here, herring muscle PJ was selected as an alternative glazing solution based on our own earlier observations that PJ from several species, including herring, are strong inhibitors of Hb-mediated lipid oxidation in a washed fish mince (Undeland et al, 2003;Sannaveerappa et al, 2007), but also based on others' observations that surface treatment of fish fillets with fish muscle-derived compounds provides stability during cold storage (Dekkers et al, 2011;Qiu et al, 2014). Qiu et al, 2014 produced silver carp protein hydrolysate from isopropanol-defatted carp meat where after sierra fish (Scomberomorus niphonius) fillets were immersed for 1 h at 4°C in a 1.5% solution of the hydrolysate, or in solutions containing 0.5% carnosine, 0.02% propyl gallate or pure distilled water (control).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from radical scavenging activity, NS-GH also had metal chelating activity and electron donating ability, which were able to prevent lipid oxidation effectively (data not shown). Qiu et al (2014) found that silver carp antioxidant peptide could prevent lipid oxidation of fish fillets during frozen storage, in which conjugated diene value, TBARS value and fluorescence compounds were reduced during the storage. Antioxidative tetrapeptide isolated from Amur sturgeon skin gelatin prevented lipid oxidation in fish mince subjected to repeated freeze-thawing, as indicated by lower TBARS formation (Nikoo et al, 2014).…”
Section: Tbarsmentioning
confidence: 98%